2005
DOI: 10.1143/ptps.157.164
|View full text |Cite
|
Sign up to set email alerts
|

Ground State Entanglement in Spin Systems

Abstract: We study the entanglement between arbitrary two spins in the XY and the antiferromagnetic Heisenberg spin chains in a uniform magnetic field. The entanglement of pairwise qubits in these models is obtained as a function of magnetic field by exact and numerical calculations. We find that the behavior of entanglement in the isotropic XY model is qualitatively the same as that in the Heisenberg model. Properties of entanglement length are also discussed. §1. IntroductionEntanglement is a crucial feature of quantu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 2 publications
3
7
0
Order By: Relevance
“…In [48] a relation between the critical field h E c for entanglement creation and the critical field h E d at which entanglement dies was proposed. A relation that is in agreement with the results from the finite size systems [49]. For quantum discord however, the comportment is different.…”
Section: Entanglement and Quantum Discordsupporting
confidence: 86%
“…In [48] a relation between the critical field h E c for entanglement creation and the critical field h E d at which entanglement dies was proposed. A relation that is in agreement with the results from the finite size systems [49]. For quantum discord however, the comportment is different.…”
Section: Entanglement and Quantum Discordsupporting
confidence: 86%
“…It is notable that there is a relationship between h E c and h c . Our results show that the critical entangled-field is and was reported in finite size systems for the first time 36 . Here we explicitly showed that this phenomenon is also observed in the thermodynamic limit.…”
Section: The Modelsupporting
confidence: 69%
“…It has been shown that at zero temperature, the entanglement between the non-nearest neighbor spins becomes finite around the quantum critical field. The entanglement remains finite even if the distance between the spin pair reaches the system size 36 . The concurrence and the quantum discord for the 2N spins were also studied in the Ising and the XXZ spin chains 38 .…”
Section: Introductionmentioning
confidence: 99%
“…In other words, there is a threshold transverse field h E c above which the 2nd neighbor spins become entangled at zero temperature. The entanglement which induced by an external magnetic field is known as the "magnetic entanglement" where reported for longitudinal magnetic fields [13,28,[59][60][61]. It is worthwhile to mention that, the phase transition at T = 0 is pinpointed by a global maximum of entanglement between both first and second neighbor spin pairs at the critical point ∆ c = 1.…”
Section: Resultsmentioning
confidence: 99%